2011
DOI: 10.1016/s1734-1140(11)70698-3
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe – a new approach in hypercholesterolemia management

Abstract: Ezetimibe is the first agent used in hypercholesterolemia treatment known to lower intestinal cholesterol uptake that is able to inhibit NPC1L1 transport proteins in the brush boarder of enterocytes and macrophages. Furthermore, it demonstrates anti-inflammatory and immunomodulatory properties and influences the expression of certain antigens. The drug is rapidly absorbed from the gastrointestinal tract and is then glucuronidated to form the active metabolite. It also undergoes extensive enterohepatic circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 73 publications
1
28
0
5
Order By: Relevance
“…NPC1L1 is the molecular target of ezetimibe, an inhibitor of cholesterol absorption that has been approved for the treatment of hypercholesterolemia (8,9). Ezetimibe binding to NPC1L1 may result in NPC1L1 protein conformational changes, thereby disturbing the interactions between NPC1L1 and free cholesterol, and ultimately inhibiting cholesterol-induced NPC1L1 endocytosis (6,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…NPC1L1 is the molecular target of ezetimibe, an inhibitor of cholesterol absorption that has been approved for the treatment of hypercholesterolemia (8,9). Ezetimibe binding to NPC1L1 may result in NPC1L1 protein conformational changes, thereby disturbing the interactions between NPC1L1 and free cholesterol, and ultimately inhibiting cholesterol-induced NPC1L1 endocytosis (6,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, after oral administration of ezetimibe, it is released from the dosage form in the upper small intestine, where it is taken up into enterocytes based on the regional expression and activity of P-gp and multidrug resistant protein 2 (MRP2) (Oswald et al, 2006a (Suchy et al, 2011). They also showed that up-regulation of intestinal P-gp in healthy subjects was associated with markedly decreased serum concentrations and a sterol-lowering effect of ezetimibe (Suchy et al, 2011;Bandyopadhyay et al, 2012). In another study, the intestinal expression of ATP-binding cassette, subfamily B, member 1 transporter (ABCB1) was inversely correlated with the effects of ezetimibe on plant sterol serum concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…It may change the shape of NPC1L1 to render it incapable of binding to sterols or interfere with the binding of free cholesterol to the cell membrane. After oral administration, it is rapidly absorbed from the gut lumen and conjugated by UDP-glucuronosyl-transferases (Bandyopadhyay et al, 2012;Lioudaki et al, 2011;Oswald et al, 2006a;Oswald et al, 2006b;Oswald et al, 2007;Phan et al, 2012;Suchy et al, 2011).…”
Section: Ezetimibe or 1-(4-fluorophenyl)-(3r)-[3-{4-fluorophenyl}-{3smentioning
confidence: 99%
“…Ezetimibe proved to be an effective drug lowering plasma LDL-C levels significantly by blocking cholesterol absorption in the small intestine [99]. To that point though, various studies showed effective LDL-C lowering in liver, cardiac and renal transplant recipients [99].…”
Section: Ezetimibementioning
confidence: 99%